Factores socioeconómicos y su relación con el aprendizaje de los estudiantes del segundo grado de primaria de la I.E. Nº 60743 Enry Herve Linares Soto, 2022 - Gonzalez Davila, Guadalupe Rosa (2023)
The present investigation emphasized determining to what extent the socioeconomic factor is related to the learning of the students of the 2nd grade of primary education of the Educational Institution No. 60743 Enry Herve Linares Soto, 2022, the population consisted of 260 students. of the Educational Institution, and the study sample consisted of 52 students from the morning and afternoon shift of the 2nd grade of primary education. This study is of a quantitative, descriptive and correlational type, the questionnaire format on socioeconomic factors obtained results in the economic, social and political dimensions, and learning was obtained with a technical evaluation sheet through the list of notes that they provided. classroom tutors for each shift. Of the students participating in this research, 53.8% are male and 46.2% are female, with participation in shifts, 55.8% in the morning shift and 44.2% in the afternoon shift, at the section level, 48 .15 from section “A” and 51.9% from section “B”. The average grade for the majority of the 2nd grade students is regular with 61.5%, followed by 26.9% bad and 11.5% good. The results in the study dimensions, economically there is 71.2% with high educational conditions of the students, socially there is 65.4% with high social relationships, and politically there is 57.7% with medium political participation. And with respect to the hypothesis raised if there is an association between both study variables, it was found that there is no significant association, because the likelihood ratio was 0.089, which compared with the level of significance α = 0.05, that is, both variables They are independent, but a significant relationship was found between the variables: learning with the sex of the students, this result being 0.049.